Analisis Beban Kerja dan Efesiensi Waktu Kerja pada Proses Produksi Tahu (Studi Kasus: Ud. Asal Lancar) - Rezinto, Fahuril; Sajiyo, Sajiyo (Jurnal Teknik Industri Terintegrasi (JUTIN), 2026)
This study analyzes physical workload and work-time efficiency in the tofu production process at UD Asal Lancar, where operations are still performed manually. A total of 12 production workers were included as research samples. Physical workload was measured using the Cardiovascular Load (CVL) method, work-time efficiency was evaluated through the Work Sampling method, and the optimal number of workers was determined using Work Load Analysis (WLA). The results show that the highest workload occurred in Worker 7, who recorded a CVL value of 53%, categorized as a heavy workload, while other workers fell into light to moderate categories. Work-time efficiency was found to be 84%, lower than the standard due to reduced effective working time caused by unproductive activities. The study recommends task redistribution, implementation of regular micro-breaks, and additional manpower in certain stages to balance workloads and improve work efficiency.